Playing dirty: the shady governance and reproduction of migrant illegality - Scheel, Stephan (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
State authorities in Europe invest immense resources in what the EU insists on calling the ‘fight against illegal migration’. Based on ethnographic research in two German cities, this paper shows that a tough approach towards illegalised migration can only be implemented through state practices that operate at the margins of, or even cross, the boundaries of what is legally permissible. This argument is developed through an analysis of informal practices that frontline staff in registry offices and migration administrations deploy to prevent, or at least disturb, illegalised migrants’ attempts to regularise their status by becoming the parent of child that is entitled to German citizenship. Drawing on the autonomy of migration approach, I use migrants’ struggles within and against Germany’s migration and citizenship regime as an epistemic device to expose three kinds of informally institutionalised counter-tactics of street-level bureaucrats that qualify as unlawfare. The analysis shows that officials, in their attempts to forestall migrants’ practices of self-legalisation, frequently resort to practices that are legally questionable or outright unlawful themselves. Ultimately, not only a tough stance on illegalised migration, but the very production of migrant illegality emerges as contagious as it implicates an illegalisation of state practices.
Keywords: Irregular Migration; Illegality; Regularization; State Crime; Street-Level Bureaucracy